Insertions/Deletions-Associated Nucleotide Polymorphism in Arabidopsis thaliana - Guo, Changjiang; Du, Jianchang; Wang, Long; Yang, Sihai; Mauricio, Rodney; Tian, Dacheng; Gu, Tingting (Frontiers in Plant Science, 2016)
Although high levels of within-species variation are commonly observed, a general mechanism for the origin of such variation is still lacking. Insertions and deletions (indels) are a widespread feature of genomes and we hypothesize that there might be an association between indels and patterns of nucleotide polymorphism. Here, we investigate flanking sequences around 18 indels (>100bp) among a large number of accessions of the plant, Arabidopsis thaliana. We found two distinct haplotypes, i.e. a nucleotide dimorphism, present around each of these indels and dimorphic haplotypes always corresponded to the indel-present/-absent patterns. In addition, the peaks of nucleotide diversity between the two divergent alleles were closely associated with these indels. Thus, there exists a close association between indels and dimorphisms. Further analysis suggests that indel-associated substitutions could be an important component of genetic variation shaping nucleotide polymorphism in Arabidopsis. Finally, we suggest a mechanism by which indels might generate these highly divergent haplotypes. This study provides evidence that nucleotide dimorphisms, which are frequently regarded as evidence of frequency-dependent selection, could be explained simply by structural variation in the genome.